Incidence of atrial fibrillation in patients with cryptogenic stroke - Abhishek Sachdeva,; Anil Bhat,; Ratinder Pal Singh,; Anand Kumar Pandey,; Rajesh Gupta,; V Manoj, Sreehari (Asian Journal of Medical Sciences, 2022)
Background: Stroke can cause serious disability and mortality among the worldwide population. Atrial fibrillation (AF) is one of the major risk factors for ischemic stroke and a common cause of cardioembolism in old age. Aims and Objectives: The aim of the study was to study the incidence of AF in patients with cryptogenic stroke (CS). Materials and Methods: A prospective and observational study on AF and stroke was carried out in the Department of Cardiology/Neurology, in a tertiary care hospital. Data were collected in the form of chief complaints, medical history, clinical examination, and treatment given in the enclosed proforma for 1 year. On follow-up, specified goals including hypertension (HTN) management, lipid management, and diabetes management were done as per current guidelines. Results: Out of 100 CS patients, 69 were male and the mean age of the patients in this study was 59±13.37 years. The incidence of AF was 11% at the end of 1 year with male predominance (64%) and a mean age of 62±12.94 years. The mean CHADS2 Score in this study group was 1.40 with a standard deviation of 1.31. Stroke reoccurred in 12% of patients at the end of 1-year follow-up. Patients with recurrent stroke were mostly elderly with a mean age of 70 years (SD=9.78, P=0.03). Conclusion: It is found that a longer duration of electrocardiographic monitoring after CS increases the proportion diagnosed with AF and should be done in selected high-risk cases, especially in patients with HTN, dyslipidemia, diabetes mellitus, chronic kidney disease, and high CHADS2 score.